Environmental six-ring polycyclic aromatic hydrocarbons are potent inducers of the AhR-dependent signaling in human cells. (November 2020) - Vondráček, Jan; Pěnčíková, Kateřina; Ciganek, Miroslav; Pivnička, Jakub; Karasová, Martina; Hýžďalová, Martina; Strapáčová, Simona; Pálková, Lenka; Neča, Jiří; Matthews, Jason; Lom, Michal Vojtíšek; Topinka, Jan; et al.
Abstract: The toxicities of many environmental polycyclic aromatic hydrocarbons (PAHs), in particular those of high-molecular-weight PAHs (with MW higher than 300), remain poorly characterized. The objective of this study was to evaluate the ability of selected environmentally relevant PAHs with MW 302 (MW302 PAHs) to activate the aryl hydrocarbon receptor (AhR), since this represents a major toxic mode of action of PAHs. A large number of the evaluated compounds exhibited strong AhR-mediated activities, in particular in human models. The studied MW302 PAHs also significantly contributed to the overall calculated AhR activities of complex environmental mixtures, including both defined standard reference materials and collected diesel exhaust particles. The high AhR-mediated activities of representative MW302 PAHs, e.g. naphtho[1, 2- k ]fluoranthene, corresponded with the modulation of expression of relevant AhR target genes in a human lung cell model, or with the AhR-dependent suppression of cell cycle progression/proliferation in estrogen-sensitive cells. This was in a marked contrast with the limited genotoxicity of the same compound(s). Given the substantial levels of the AhR-activating MW302 PAHs in combustion particles, it seems important to continue to investigate the toxic modes of action of this large group of PAHs associated with airborne particulate matter. Graphical abstract: Image 1 Highlights: Effects of environmental PAHs with MW302 on activation of the AhR were studied. MW302 PAHs were potent agonists of the AhR in rat and human reporter gene assays. MW302 PAHs induced or repressed relevant AhR-responsive genes in human lung cells. MW302 PAHs repressed estrogenic responses in human cells in AhR-dependent manner. AhR activation could be a major toxic mode of action of environmental MW302 PAHs. Abstract : Polycyclic aromatic hydrocarbons with molecular weight 302, associated with particulate emissions, were identified as potent agonists of the aryl hydrocarbon receptor.